A 3D Approach for the Virtual Commissioning of Processing Plants - Nikolai Striffler; Tobias Voigt (IEEE Access)
This paper presents a novel 3D approach for virtual commissioning (VC) in process engineering, utilizing a semi-automated model generation methodology based on 3D MCAD data. Current VC practices primarily benefit larger manufacturing systems due to the complexity and time-intensive nature of model generation, which poses challenges for broader adoption, especially in small and medium-sized enterprises. Our approach addresses this by proposing a 3D simulation model architecture that integrates physics-based simulation environments, enabling efficient and accurate generation of dynamic simulation models. By leveraging a physics engine, the proposed method automatically derives essential parameters and system topology, thereby significantly reducing the manual modeling effort. The simulation model is designed to depict complex fluid and material flows within a 3D environment, facilitating realistic, real-time interaction and improved visualization for VC. This paper further evaluates the method’s accuracy through a representative case study involving a liquid food processing setup, demonstrating high fidelity in dynamic behavior and alignment with physical processes. The results indicate that this approach offers substantial potential for improving virtual engineering and commissioning workflows, enhancing simulation model fidelity, and promoting interdisciplinary collaboration in process plant development. This development promises an adaptable, user-friendly tool that can advance the integration of VC in diverse engineering fields, particularly where hybrid production processes intersect.